Powdery mildew resistance of Nordic spring bread wheat accessions from the collection of the Vavilov Institute (VIR) - T. V. Lebedeva (Труды по прикладной ботанике, генетике и селекции, 2020)
Background. Powdery mildew is one of the harmful and destructive foliar diseases of cereal crops, caused by the fungus Вlumeria graminis (DC.) E.O. Speer f. sp. tritici Em. Marchal. Annual harvest losses may reach 10–15%, and up to 30% in an epidemic year. The VIR collection contains rich diversity of wheat, a valuable source of original material for wheat resistance breeding programs.The aim of this study was to generalize the results of long-term field and laboratory investigations on powdery mildew resistance in spring bread wheat of Nordic origin from the VIR collection and search for accessions resistant in all development phases.Materials and methods. Powdery mildew resistance was analyzed in 279 accessions originated from Sweden, Finland, Norway and Denmark. The tests were performed from 1961 to 2019 against a natural population of the fungus in VIR’s experimental field (Pushkin, St. Petersburg). Field and laboratory studies were carried out in accordance with the guidelines developed by VIR.Results. The analysis of the field data on powdery mildew resistance in spring bread wheat accessions against the Pushkin population of the fungus showed that many Nordic accessions were resistant from 1970 till 1990. These data were retested in 2012–2013. One hundred and five accessions of old landraces and modern cultivars of Nordic origin were studied under field and laboratory conditions for their response to a natural population of the fungus. Accessions resistant in all phases of plant development were identified.Conclusion. Swedish cultivars ‘Sunnan’ (k-58177), ‘Canon’ (k-60992), ‘Sober’ (k-61080) ‘Dragon’ (k-61515) and ‘Dacke’ (k-63479) preserved their resistance to the powdery mildew population beginning from 1993. Spring bread wheat cultivars ‘SW Vals’ (k-64436), ‘SW Milljet’ (k-64434), ‘SW Estrad’ (k-64435), ‘SW Vinjet’ (k-64436), ‘Zebra’ (k-64707), ‘SW Kungsjet’ (k-66036), ‘SW Kronjet’ (k-66097) and ‘Boett’ (k66353) demonstrated adult and seedling resistance in the period from 2005 to 2019.